2022
DOI: 10.3389/fmicb.2022.830209
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenemase-Producing Extraintestinal Pathogenic Escherichia coli From Argentina: Clonal Diversity and Predominance of Hyperepidemic Clones CC10 and CC131

Abstract: Extraintestinal pathogenic Escherichia coli (ExPEC) causes infections outside the intestine. Particular ExPEC clones, such as clonal complex (CC)/sequence type (ST)131, have been known to sequentially accumulate antimicrobial resistance that starts with chromosomal mutations against fluoroquinolones, followed with the acquisition of blaCTX–M–15 and, more recently, carbapenemases. Here we aimed to investigate the distribution of global epidemic clones of carbapenemase-producing ExPEC from Argentina in represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…However, subclade C1 presents bla CTX-M-14 or bla CTX-M-27 ESBL genes, while on the other hand, subclade C2, which has a single nucleotide polymorphism (SNP) at fimH30, is mainly associated with bla CTX-M-15 . The bla CTX-M-27 positive subset of C1, referred to as subclade C1-M27, recently became prominent in Japan, Canada, Germany and China [20,46,[80][81][82]. In Iran, a comparative study on MDR ST131 and non-ST-131 clones reported that both were associated with bla TEM , bla SHV , bla CTX-M , bla OXA-48 genes, as well as with plasmid-mediated quinolone resistance (PMQR) determinants (bifunctional aminoglycoside acetyltransferase-Ib-cr [aac6 -Ib-cr] and Qnr protective proteins [qnrB, qnrS] [83].…”
Section: Cc/st131 the Worldwide Predominant High-risk Clonementioning
confidence: 99%
See 4 more Smart Citations
“…However, subclade C1 presents bla CTX-M-14 or bla CTX-M-27 ESBL genes, while on the other hand, subclade C2, which has a single nucleotide polymorphism (SNP) at fimH30, is mainly associated with bla CTX-M-15 . The bla CTX-M-27 positive subset of C1, referred to as subclade C1-M27, recently became prominent in Japan, Canada, Germany and China [20,46,[80][81][82]. In Iran, a comparative study on MDR ST131 and non-ST-131 clones reported that both were associated with bla TEM , bla SHV , bla CTX-M , bla OXA-48 genes, as well as with plasmid-mediated quinolone resistance (PMQR) determinants (bifunctional aminoglycoside acetyltransferase-Ib-cr [aac6 -Ib-cr] and Qnr protective proteins [qnrB, qnrS] [83].…”
Section: Cc/st131 the Worldwide Predominant High-risk Clonementioning
confidence: 99%
“…As an interesting result, a strain referenced as ECO14 of ST131 exhibited resistance to colistin (MIC ≥ 4 µg/mL), but it lacked mcr. It developed colistin resistance due to seven chromosomal mutations in the pmrB and pmrA genes (phosphoetanolamin transferase coding genes) [20].…”
Section: Cc/st131 the Worldwide Predominant High-risk Clonementioning
confidence: 99%
See 3 more Smart Citations